PERAN PEMERINTAH DESA DALAM PENGEMBANGAN POTENSI MASYARAKAT DESA MEDE KECAMATAN TOBELO UTARA KABUPATEN HALMAHERA UTARA - Malani, Lexy Febrison; Tumengkol, Selvie M.; Lumintang, Juliana (HOLISTIK, Journal Of Social and Culture, 2021)
National Development is a reflection of the will to continuously improve the welfare and prosperity of the Indonesian people in a fair and equitable manner, as well as develop people's lives and the implementation of a developed and democratic country based on Pancasila. The development that was built on the practice of Pancasila is the development of the whole Indonesian people and the development of the entire Indonesian society, with Pancasila as the basis, objectives, and guidelines.The economic progress of villages and all regions or in other words equalization of economic progress is an important target in the country's economic development. Village potential management aims to encourage initiatives, movements, village community participation for the development of village potentials and assets for the common welfare. The potential in this paper is the power, strength, ability and capability that have the possibility to be developed.Management of village potential by the village government, in this case the physical potential in Mede Village North Tobelo Subdistrict, North Halmahera Regency is less optimal realization due to the lack of provision of facilities and infrastructure for sand miners. In order to develop the village's original income or village assets that become the main source in village development and for the welfare of the village community.The problems that occurred in Mede Village, North Tobelo District, North Halmahera Regency resulted from several factors, among others, lack of knowledge about village community empowerment by the government, lack of control from the local government, inadequate facilities and infrastructure in the development of village community potential, and lack of business capital that is not fully supported.Keywords: potential, village, role